MULTIBAND WAVELENGTH-DIVISION DEMULTIPLEXING WITH A CASCADED SUBSTRATE-MODE GRATING STRUCTURE - TSAI, YK; HUANG, YT; SU, DC (My University, 1995)
A multiband wavelength-division-demultiplexing (WDDM) structure, which incorporates cascaded substrate-mode holograms, is presented. The method can be used to design a WDDM device that consists of two or more layers of fundamental units (i.e., substrate-mode holograms). The fundamental unit is based on a diffracted grating and a substrate that include angular dispersion, wavelength bandwidth, and total internal reflection, which can be used to separate optical signals of different wavelengths. We have designed and built a multiband WDDM device, incorporating cascaded substrate-mode holograms in dichromated gelatin.
Keywords: WAVELENGTH-DIVISION DEMULTIPLEXING; SUBSTRATE-MODE HOLOGRAM